Validation of a Non-Targeted LC-MS Approach for Identifying Ancient Proteins: Method Development on Bone to Improve Artifact Residue Analysis - Barker, Andrew; Dombrosky, Jonathan; Chaput, Dale; Venbles, Barney; Wolverton, Steve; Stevens, Stanley M. (Ethnobiology Letters, 2015)
Identification of protein residues from prehistoric cooking pottery using mass spectrometry is challenging because proteins are removed from original tissues, are degraded from cooking, may be poorly preserved due to diagenesis, and occur in a palimpsest of exogenous soil proteins. In contrast, bone proteins are abundant and well preserved. This research is part of a larger method-development project for innovation and improvement of liquid chromatography – mass spectrometry analysis of protein residues from cooking pottery; here we validate the potential of our extraction and characterization approach via application to ancient bone proteins. Because of its preservation potential for proteins and given that our approach is destructive, ancient bone identified via skeletal morphology represents an appropriate verification target. Proteins were identified from zooarchaeological turkey (Meleagris gallopavo Linnaeus Phasianidae), rabbit (Lagomorpha), and squirrel (Sciuridae) remains excavated from ancient pueblo archaeological sites in southwestern Colorado using a non-targeted LC-MS/MS approach. The data have been deposited to the ProteomeXchange Consortium with the dataset identifier PXD002440. Improvement of highly sensitive targeted LC-MS/MS approaches is an avenue for future method development related to the study of protein residues from artifacts such as stone tools and pottery.